Evaluation of emissions and exposures at workplaces using desktop 3-dimensional printer - Stefaniak, A B; Johnson, A R; du Preez, S; Hammond, D R; Wells, J R; Ham, J E; LeBouf, R F; Menchaca, K W; Martin, Jr, S B; Duling, M G; Bowers, L N; Knepp, A K; et al. (ACS Chemical Health & Safety., 2019)
There is a paucity of data on additive manufacturing process emissions and personal exposures in real-world workplaces. Hence, we evaluated atmospheres in four workplaces utilizing desktop "3-dimensional" (3-d) printers [fused filament fabrication (FFF) and sheer] for production, prototyping, or research. Airborne particle diameter and number concentration and total volatile organic compound concentrations were measured using real-time instruments. Airborne particles and volatile organic compounds were collected using time-integrated sampling techniques for off-line analysis. Personal exposures for metals and volatile organic compounds were measured in the breathing zone of operators. All 3-d printers that were monitored released ultrafine and fine particles and organic vapors into workplace air. Particle number-based emission rates (#/min) ranged from 9.4 × 10 to 4.4 × 10 (n = 9samples) for FFF3-d printers and from 1.9 to 3.8 × 10 (n = 2 samples) for a sheer 3-d printer. The large variability in emission rate values reflected variability from the printers as well as differences in printer design, operating conditions, and feedstock materials among printers. A custom-built ventilated enclosure evaluated at one facility was capable of reducing particle number and total organic chemical concentrations by 99.7% and 53.2%, respectively. Carbonyl compounds were detected in room air; however, none were specifically attributed to the 3-d printing process. Personal exposure to metals (aluminum, iron) and 12 different organic chemicals were all below applicable NIOSH Recommended Exposure Limit values, but results are not reflective of all possible exposure scenarios. More research is needed to understand 3-d printer emissions, exposures, and efficacy of engineering controls in occupational settings.